Plasmodium falciparum DHFR and DHPS Mutations Are Associated With HIV-1 Co-Infection and a Novel DHPS Mutation I504T Is Identified in Western Kenya - Torrevillas, Brandi K.; Garrison, Sarah M.; McKeeken, Alexander J.; Patel, Dharmeshkumar; Van Leuven, James T.; Dizon, Nathaniel I.; Rivas, Karina I.; Hathaway, Nicholas J.; Bailey, Jeffrey A.; Waitumbi, John N.; Kifude, Carolyne M.; Oyieko, Janet; et al. (Frontiers in Cellular and Infection Microbiology, 2020)
Antifolate resistance is significant in Kenya and presumed to result from extensive use and cross-resistance between antifolate antimalarials and antibiotics, including cotrimoxazole/Bactrim used for HIV-1 chemotherapy. However, little is known about antifolate-resistant malaria in the context of newly diagnosed HIV-1 co-infection prior to administration of HIV-1 chemotherapy. Blood samples from a cross-sectional study of asymptomatic adult Kenyans enrolled during voluntary HIV testing were analyzed by PCR for Plasmodium spp. More than 95% of volunteers with identifiable parasite species (132 HIV-1 co-infected) were infected with Plasmodium falciparum alone or P. falciparum with Plasmodium ovale and/or Plasmodium malariae. Deep sequencing was used to screen for mutations in P. falciparum dhfr (N51I, C59R, S108N, I164L) and dhps (S436H, A437G, K540E, A581G) from 1133 volunteers. Individual mutations in DHPS but not DHFR correlated with HIV-1 status. DHFR haplotype diversity was significantly different among volunteers by gender and HIV-1 status. DHPS haplotype diversity by HIV-1 status was significantly different between volunteers paired by age and gender, indicating that patterns of resistance were independent of these variables. Molecular simulations for a novel DHPS mutation (I504T) suggested that the mutated protein has increased affinity for the endogenous ligand DHPPP and decreased affinity for drug binding. A sub-group of monoclonal infections revealed that age and parasitemia were not correlated and enabled identification of a rare septuple-mutant haplotype (IRNL-HGEA). In our study, adult Kenyans newly diagnosed with HIV-1 infection were predominantly infected with moderately resistant P. falciparum, with patterns of infecting parasite genotypes significantly associated with HIV-1 status. Together with the discovery of DHPS I504T, these data indicate that antifolate resistance continues to evolve in Kenya. Further, they highlight the need to understand the effects of associated mutations on both fitness and resistance of P. falciparum in the context of HIV-1 co-infection to better inform treatment for asymptomatic malaria.